2003
DOI: 10.1186/1478-7547-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Costs of stroke and stroke services: Determinants of patient costs and a comparison of costs of regular care and care organised in stroke services

Abstract: Background: Stroke is a major cause of death and long-term disability in Western societies and constitutes a major claim on health care budgets. Organising stroke care in a stroke service has recently been demonstrated to result in better health effects for patients. This paper discusses patient costs after stroke and compares costs between regular and stroke service care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Here costs are reduced from €10,018 to €5,777, on average. This confirms earlier findings on the reduced length of stay [ 13 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Here costs are reduced from €10,018 to €5,777, on average. This confirms earlier findings on the reduced length of stay [ 13 ].…”
Section: Resultssupporting
confidence: 93%
“…We considered the impact on informal care in this study elsewhere [ 14 ]. Costs of care for the first six months after stroke were based on patient level resource use from the EDISSE study [ 13 ], and resource costs/prices of 2003 [ 23 ]. Because length of stay at different locations was the most important cost driver during this period [ 13 ], first, inpatient costs were calculated using original length of stay data and 2003 nursing day prices.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study that has estimated the potential public health impact of a substantial salt reduction in a single food category. Since considerable acute and long-term health care costs and productivity losses are involved with HF, stroke [ 41 ] and AMI [ 42 ], it is likely that reducing respective incident cases can significantly reduce related health care costs and productivity losses. This case study shows that a substantial and achievable salt reduction in soups in the Netherlands as part of an overall salt reduction strategy, could potentially have an impact, albeit small, on public health.…”
Section: Discussionmentioning
confidence: 99%
“…research [18,68] has shown that VASs provide valid Data were analyzed using SPSS (version 12.0.1). Responknown about the situation and experiences of padents answered questions about socioeconomic statients on waiting lists for nursing home or residential tus, health, well-being, intermittent care use, care care, let alone on waiting lists for home care.…”
Section: Effects Of Waiting Measures To Reducementioning
confidence: 99%